Eco-Theology: Formulating the Concept of Maqāṣid al-Sharī‘ah in the Context of the Environmental Crisis - Jumaah Jumaah; Maimun Maimun; Suhirman Suhirman (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
The accelerating global environmental crisis including ecosystem degradation, climate change, and rapid biodiversity loss demands a more integrated religious and ethical response. This study investigates how Maqāṣid al-Sharī‘ah can be reformulated as a normative foundation for eco-theology capable of addressing escalating ecological damage that threatens human survival and planetary stability. The core problem examined is the insufficient alignment between Islamic legal objectives and the urgent need for environmental preservation. Using a qualitative-descriptive approach supported by literature review and textual analysis of classical Islamic sources and contemporary environmental scholarship, this research constructs an ecological extension of the maqāṣid framework. The findings indicate that strengthening ḥifẓ al-nafs, ḥifẓ al-māl, and the emerging category of ḥifẓ al-bī’ah provides a robust ethical and legal basis for embedding ecological consciousness within Islamic thought and practice. The study concludes that an eco-theological formulation grounded in maqāṣid offers a transformative paradigm in which environmental protection becomes not merely a scientific or policy concern but a moral-religious obligation essential for ensuring justice, wellbeing, and sustainability for present and future generations